Strategy and sustainability: 6 'P's for socially responsible strategy - Gond, Jean-Pascal; Spicer, Andre (Henry Stewart Talks, 2013)
Wealth and poverty in London, Lakehouse company, Closing the gap between training and employment, Rethinking the purpose of strategy, The shareholder value model and the critique of corporate social responsibility – Milton Friedman’s assumptions, Shareholder value is a result, not a strategy – Shareholder vs. stakeholder view, CSR and strategy as perspective – CSR and strategy as plan, Marks & Spencer – CSR and strategy as position, Inside-out analysis (Porter and Kramer 2006), Outside-in analysis (Porter and Kramer 2006) – CSR and strategy as ploy, Unilever and the Marine Stewardship Council, CSR and strategy as pattern – “Energy-Corp”
Reviewed at 2021/02/26